Notes on the hematology of free-living phrynops geoffroanus (testudines: Chelidae) in polluted rivers of southeastern Brazil - Ferronato, Bruno O. (2009)
Phrynops geoffroanus (Schweigger, 1812) is the freshwater turtle with the widest geographical distribution in South America. During 2006, physical examination and hematological evaluation were performed on free-ranging turtles from two polluted rivers, the Piracicaba River (n = 51) and its tributary Piracicamirim (n = 42), in southeastern Brazil. Red blood cell and thrombocyte counts, mean corpuscular volume and mean corpuscular hemoglobin levels differed in turtles from the two water courses. Although free-ranging turtles showed ectoparasites and boat propeler lesions, animals apparently had no signs of clinical disease. In spite of our results, further monitoring of the demography and health status of Phrynops geoffroanus in anthropogenically altered environments is recommended.